Ocular fundus changes and association with systemic conditions in systemic lupus erythematosus - Meng, Lihui; Wang, Yinhan; Yang, Zhikun; Lin, Shiqun; Wang, Yuelin; Chen, Huan; Zhao, Xinyu; Chen, Youxin (Frontiers in Immunology, 2024)
Systemic lupus erythematosus (SLE) is an autoimmune disease that affects multiple organs and systems. Ocular involvement is estimated to manifest in one-third of individuals with SLE, of which lupus retinopathy and choroidopathy represent the severe subtype accompanied by vision impairment. Advancements in multimodal ophthalmic imaging have allowed ophthalmologists to reveal subclinical microvascular and structural changes in fundus of SLE patients without ocular manifestations. Both ocular manifestations and subclinical fundus damage have been shown to correlate with SLE disease activity, and in some patients even precede other systemic injuries as the first presentation of SLE. Moreover, ocular fundus might serve as a window into the state of systemic vasculitis in patients with SLE. Given the similarities of the anatomy, physiological and pathological processes shared among ocular fundus and other vital organ damage in SLE, such as kidney and brain, it is assumed that ocular fundus involvement has implications in diagnosis and evaluation of other systemic impairments. Therefore, evaluating the fundus characteristics of SLE patients not only contributes to early diagnosis and intervention of potential vision damage, but also holds considerate significance for the evaluation of SLE vasculitis state and prediction of other systemic injuries.